Study on Fluid-Lining-Rock Coupling Interaction of Diversion Tunnel under Seismic Load - Jian Deng; Ming Xiao; Juntao Chen; Bingbing Xie; Yang Yang (Shock and Vibration)
Fluid-lining-rock coupling interaction of diversion tunnel under seismic load is a critical problem in seismic research which should be solved urgently. Based on the explicit finite element method for dynamic analysis of single-phase fluid and solid medium and combining with the boundary conditions of coupling interface, a dynamic explicit finite element solving format of diversion tunnel considering fluid-lining coupling interaction is established. In light of the basic theory of dynamic contact force method and applying the nonlinear hyperbolic constitutive model of contact surface, a dynamic explicit finite element time-domain integral equation of combined bearing of lining and surrounding rocks, which takes the bond-slip behavior of the contact surface into account, is put forward. Meanwhile, considering the dynamic interaction process of inner water and lining, lining and surrounding rocks, an explicit finite element numerical simulation analysis method of fluid-lining-rock coupling interaction of diversion tunnel under seismic load is presented. The calculation results of case study reasonably reflect the seismic response characteristics of diversion tunnel, and an effective analysis method is provided for the aseismic design of hydraulic tunnel.